Refugee, Migrant and Ethnic Minority Health - Srivastava, David Shiva (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
International migration, particularly to Europe, has increased in the last few decades, making research on aspects of this phenomenon, including numbers, challenges, and successes, particularly vital. This Special Issue highlights this necessary and relevant area of research. It presents 37 articles including studies on diverse topics relating to the health of refugees and migrants. Most articles (28) present studies focusing on European host countries. The focus on Europe is justified if we take into consideration the increased number of refugees and migrants who have come to Europe in recent years. However, there are also articles which present studies from countries in other continents. The topics discussed in the Issue include healthcare utilization, infectious diseases, mother and child health, mental health, and chronic diseases. Finding from the included articles indicate that further development of guidelines and policies at both local and international levels is needed. Priorities must be set by encouraging and funding in-depth research that aims to evaluate the impact of existing policies and interventions. Such research will help us formulate recommendations for the development of strategies and approaches that improve and strengthen the integration of migrants and refugees into the host countries.